Influence of Fusarium oxysporum-resistant pumpkin rootstock on the productivity of the F1 Asylum cucumber hybrid - Shoibekova Alima; Nusipzhanov Nurdan; Jantassov Serik (Caspian Journal of Environmental Sciences)
We examined five pumpkin cultivars (including three selected by the Kazakh Institute of Fruit and Vegetable Growing) for resistance to Fusarium. Among resistant rootstocks to the Fusarium pathogen, we distinguished Mozoleevskaya 10, Stofuntovaya, and Karina cultivars for further work. The results showed that when grafting cucumber on pumpkin, the best rootstock options compared to the root-related standard of the cucumber hybrid Asylum were the pumpkin cultivars Karina and Stofuntovaya. Their early yield indicators were in the range of 3.46 and 3.39 kg m-2. It exceeded the standard by 36.7% and 33.9%, respectively. In terms of total productivity, the grafting varieties for the pumpkin cultivars, i.e., Karina and Stofuntovaya also showed high yields: 27.56 kg m-2 and 26.65 kg m-2 respectively, which significantly exceeded the rootstock standard by 42.38% and 36.68%, respectively.